Cysts of Mandible and Maxilla. Etiology, Diagnostic Tools and Treatment Possibilities - N. Mahdian; T. Dostálová; M. Hubáček; R. Hippmann; J. Nedoma (Czech Dental Chamber, 2011)
This article is focused on summarizing the findings, dealing with the development, growth and classification of jaw cysts in dentistry. The main focus of the article was to search for literature of the most frequent cysts, namely radicular and follicular cysts. Main emphasis is placed on the mechanism of their formation and growth. Until today there is no unified division, there are multiple possibilities for classification. The review includes the possibility of radiological diagnosis, which in recent years has undergone great development. This work is also being explored in therapy, that has undergone numerous changes with appearing new augmentation materials.